IMPROVING STUDENTS’ WRITING ABILITY THROUGH FOLKTALES - NUR, HASRIATI (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
The objective of the research aims to find out whether the use of folktales can improve the students’ writing ability or not.Quasi-experimental design was applied in this research with two classes of the students. The first class as an experimental class and the second as a control class that was given different treatment. The instrument of this research was a written test. The population of this research was the first year students of SMA Negeri 2 Watampone, academic year 2012-2013. The number of population was 420 students consisted of 14 classes. A sample of this research was taken by using cluster random sampling technique; there were 60 students as sample, 30 students in X-9 as experimental class and 30 students in X-10 as control class. Data were collected through written test administered in the pretest and posttest. The mean score of pretest in experimental class is 47.93 and mean score of posttest is 73.5. While the mean score of pretest in control class is 52.36 and mean score of posttest is 66.37. It can be conclude that there is significant difference of the students after the use of folktales in improving their writing ability.